On the modelling of the epidemic processes - Bolshev, L.; Kruopis, J. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Н. Большев, Ю. И. Круопис. К вопросу о моделировании эпидемических процессовL. Bolševas, J. Kruopis. Epideminių procesų modeliavimo klausimu